Baseline hyponatremia does not predict two-year mortality in patients with chronic peritoneal dialysis. (October 2014) - Chen, Kuan-Hsing; Chen, Chao-Yu; Lee, Cheng-Chia; Weng, Chu-Man; Hung, Cheng-Chieh
Abstract Purpose: Hyponatremia is a common electrolyte abnormality in a variety of medical conditions. Lower predialysis serum sodium concentration is associated with an increased risk of death in oligoanuric patients on hemodialysis. However, whether hyponatremia affects the short-term mortality in chronic peritoneal dialysis (CPD) patients remains unclear. Methods: We conducted a cross-sectional and two-year follow-up review retrospectively, and 318 patients with CPD were enrolled in a medical center. Serum sodium levels were measured at baseline and categorized as quartile of Na: quartile 1 (124–135 mEq/L), quartile 2 (136–139), quartile 3 (140–141) and quartile 4 (142–148). Mortality and cause of death were recorded for longitudinal analyses. Results: The patients with higher quartile (higher serum sodium) had a trend of lower age, peritoneal dialysis (PD) duration, co-morbidity index, D/P Cr and white blood cell counts and higher renal Kt/Vurea (Kt/V) and serum albumin level. Stepwise multiple linear regression analysis showed that serum sodium level was positively associated with albumin, residual renal Kt/V and negatively associated with age and PD duration in CPD patients. After two-year follow-up, stepwise multivariate Cox proportional hazards model demonstrated that age, co-morbidity index and serum albumin were the significant risk factors for all-cause two-year mortality, but not serum sodium levels. Conclusions: Serum sodium level in CPD patients is associated with nutritional status, residual renal function and duration of PD. However, baseline serum sodium level is not an independent predictor of two-year mortality in CPD patients.